Construction and Antidrug Resistant Bacteria Performance of Nano Antibacterial Dressings - Taylor, Richard; Moor, Susan; Diggory, Cedric (Journal of Functional Materials and Applied Engineering, 2024)
Black phosphorus (BP) and monolayer MXene/V2CTx nanosheets, both prepared via the liquid‑phase delamination method, were mixed to fabricate MXene/BP composite (AC) by a hydrothermal method. Characterization of the composite was carried out with SEM, TEM, XRD, and a multi-angle particle-size and high-sensitivity zeta-potential analyzer. The resulting AC was then incorporated into poly(lactic-co-glycolic acid) (PLGA), from which nano-antibacterial dressings (PLGA-AC) were produced via electrospinning. The dressings were tested by SEM and an optical contact‑angle measuring instrument. In‑vitro antibacterial assays, in‑vitro cell culture experiments and hemolysis tests were performed to evaluate the reactive oxygen species (ROS)‑generating capacity, antibacterial activity and biocompatibility of PLGA‑AC. The results show that monolayer MXene nanosheets are homogeneously distributed on the BP surface, and the two components are combined by van der Waals forces. PLGA‑AC exhibits excellent hydrophilicity with a water contact angle of 52.05o. Under ultrasonic irradiation, PLGA‑AC possesses outstanding ROS‑generating capacity, achieving a clearance rate of over 99 % against Escherichia coli. PLGA‑AC also displays favorable cytocompatibility and blood compatibility, with a hemolysis rate of merely 0.97 % toward rabbit red blood cells.